An exact solution of MHD hybrid nanofluid over a stretching surface embedded in porous medium in the presence of thermal radiation and slip with suction - Saupi, Suhaila; Abd Ghani, Aniza; Md Arifin, Norihan; Rosali, Haliza; Wahid, Nur Syahirah (Semarak Ilmu Publishing, 2022)
A comprehensive study of magnetohydrodynamics (MHD) hybrid copper-alumina nanofluid flow towards a permeable stretching sheet embedded in porous medium is analyzed analytically. The flow problem is mathematical modeled into nonlinear partial differential equations, which are reduced into ordinary differential equations via similarity transformation. The analytical solutions for momentum and energy equations are found. The effects of the porosity on velocity and temperature profiles are analyzed graphically, while the skin friction coefficient and the local Nusselt number are displayed in data tabulation. The results show that increasing the porosity parameter decrease the skin friction coefficient and heat transfer rate.